1995
DOI: 10.1002/bjs.1800820509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course after transanal advancement flap repair of perianal fistula in patients with Crohn's disease

Abstract: A total of 36 rectal advancement flap repairs were performed in 32 patients with perianal Crohn's disease. There were 12 anovaginal and 20 trans-sphincteric fistulas. Patients were followed prospectively for a mean of 19.5 months to evaluate postoperative recurrence rate. The prognostic influence of fistula type, rectal disease, intestinal disease and faecal diversion on recurrence was assessed. Four of 36 repairs showed primary failure, the operated fistula recurred in 11 patients after a median of 7 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 13 publications
2
82
0
7
Order By: Relevance
“…Seventeen out of twenty-four (71%) patients achieved primary healing after initial flap repair and a total of 22/24 patients had healing after further repairs. Similarly, Makowiec et al [25] and Crim et al [26] reported successful healing of RVF secondary to CD in 5/12 and 10/14 patients, respectively with this technique.Ruffolo et al [27] stress that the advantages of a flap procedures are a low chance of: producing a keyhole deformity, worsening fecal incontinence, or aggravation of patient's symptoms in case of failure. Additionally, there is no perineal wound and the presence of a stoma is not mandatory.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Seventeen out of twenty-four (71%) patients achieved primary healing after initial flap repair and a total of 22/24 patients had healing after further repairs. Similarly, Makowiec et al [25] and Crim et al [26] reported successful healing of RVF secondary to CD in 5/12 and 10/14 patients, respectively with this technique.Ruffolo et al [27] stress that the advantages of a flap procedures are a low chance of: producing a keyhole deformity, worsening fecal incontinence, or aggravation of patient's symptoms in case of failure. Additionally, there is no perineal wound and the presence of a stoma is not mandatory.…”
mentioning
confidence: 77%
“…Seventeen out of twenty-four (71%) patients achieved primary healing after initial flap repair and a total of 22/24 patients had healing after further repairs. Similarly, Makowiec et al [25] and Crim et al [26] reported successful healing of RVF secondary to CD in 5/12 and 10/14 patients, respectively with this technique.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…Eight retrospective30 37, 39 40, 42, 43, 44 46 and two prospective observational38 41 studies reported the outcome of mucosal advancement flaps in both Crohn's and cryptoglandular perianal fistulous disease. Of the 590 reported procedures, 204 were performed for Crohn's fistula.…”
Section: Resultsmentioning
confidence: 99%